Animals learn to draw and color 26 wild creatures, step by easy step, shape by simple shape! - Fisher, Diana (Laguna Hills, Calif Walter Foster, 2005)
Presents basics steps to drawing and coloring tips for creating pictures of wild creatures, including koalas, lemurs, wildebeest, crocodiles, tigers, and more
1
Keywords: Animals in art; Drawing -- Technique